The Impact of Entrepreneurial Orientation and Strategic Networks on the Sustainability of MSMEs in Bogor - Puti Khairani Rijadi; Rani Eka Arini; Ilham Akbar Bunyamin (West Science Interdisciplinary Studies, 2026)
This study examines the effects of entrepreneurial orientation and strategic networks on the sustainability of micro, small, and medium enterprises (MSMEs) in Bogor. A quantitative explanatory research design was employed using data collected from 130 MSME owners and managers selected through purposive sampling. The research instrument consisted of a structured questionnaire measured using a five-point Likert scale. Data were analyzed using SPSS version 25 through descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression, partial t-tests, an F-test, and the coefficient of determination. The results show that entrepreneurial orientation has a positive and significant effect on MSME sustainability. Strategic networks also have a positive and significant effect on MSME sustainability Simultaneously, entrepreneurial orientation and strategic networks significantly affect MSME sustainability, as indicated by an F-value of 122.467 and a significance value below 0.001. The coefficient of determination of 0.658 indicates that 65.8% of the variation in MSME sustainability is explained by entrepreneurial orientation and strategic networks, while the remaining 34.2% is influenced by other factors outside the research model. These findings demonstrate that MSME sustainability depends on the integration of internal entrepreneurial capabilities and external relational resources. MSME owners should strengthen innovation, proactive behavior, calculated risk-taking, and strategic collaboration with relevant stakeholders to improve long-term business resilience and competitiveness.